Dangerous minds - Pfeiffer, Michelle, 1957-; Dzundza, George; Smith, John N., 1943-; Simpson, Don, 1945-1996.; Bruckheimer, Jerry; Hollywood Pictures (Burbank, Calif. Hollywood Pictures Home Video: Distributed by Buena Vista Home Video, 1996)
When an ex-Marine becomes a high school teacher, she is assigned to a tough class of inner-city teenagers.
Rated R.
Closed captioned for the hearing impaired.
Director, John N. Smith ; producers, Don Simpson & Jerry Bruckheimer ; screenplay, Ronald Bass ; based on "My posse don't do homework" by Louanne Johnson ; score composed and produced by Wendy & Lisa.
Michelle Pfeiffer, George Dzundza.
Digital ; hi-fi Dolby surround stereo.
Keywords: High school teachers -- Drama